PENDEKATAN HUMANISTIK DALAM PEMBELAJARAN ABAD 21 - Indiani, Ni Made; Ida Ayu Gde Yadnyawati (Guna Widya: Jurnal Pendidikan Hindu, 2024)
The 21st century learning paradigm leads towards: a) students center learning; b) learning is not centered in one place c). reducing the need for study space facilities, (physical) and paperless. d) training/socialization tends to be related to the use of applications (skills). e) the demand to be able to read and understand of big data (data literacy, technology literacy, and human literacy). This change in learning models is definitely accompanied by changes in educational management. Implementation of education management is carried out jointly between the government, educational units, (school principals & teachers), parents and students. This can be done through collaboration, responsibility and ethics by applying a humanistic approach. The method used is through literature review or reviewing literature that is relevant to technohumanistic learning. The conclusion obtained is that the government, educational units, school principals, teachers, parents must be able to create regulations and educational facilities that are safe and comfortable for children or provide learning places (schools) that are child-friendly, free from bullying problems, violence, intolerance and discrimination. Key words : 21st century learning; education management; humanistic approach; child friendly school.